1999
DOI: 10.1046/j.1365-2141.1999.01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Three major G6PD‐deficient polymorphic variants identified among the Mauritian population

Abstract: We report the results of the first epidemiological study investigating glucose 6‐phosphate dehydrogenase (G6PD) deficiency among the heterogenous Mauritian population. Mauritius has a population of approximately 1 million, and of these 66.8% are Indo‐Mauritian (of Indian origin), 27.9% are Creoles (of African ancestry) and 2.1% are Sino‐Mauritian, predominantly of Chinese origin. Of the 1435 Mauritian males tested, 73 (5.1%) were G6PD deficient. However, the prevalence varied considerably between the two major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…We have also found G6PD Mahidol in two Indian males in Myanmar. Although this mutation has been reported in an Indian immigrant in Mauritius (Kotea et al 1999), it has never been documented on the Indian subcontinent (Kaeda et al 1995). We consider that the G6PD Mahidol mutation in the Indians in Myanmar may have occurred independently in India, because intermarriage between Indians and other ethnic groups in Myanmar is rare.…”
Section: Discussionmentioning
confidence: 95%
“…We have also found G6PD Mahidol in two Indian males in Myanmar. Although this mutation has been reported in an Indian immigrant in Mauritius (Kotea et al 1999), it has never been documented on the Indian subcontinent (Kaeda et al 1995). We consider that the G6PD Mahidol mutation in the Indians in Myanmar may have occurred independently in India, because intermarriage between Indians and other ethnic groups in Myanmar is rare.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, six other variants were found but at much lower frequencies: G6PD Vanua Lava 383 T>C (3.4%), G6PD Coimbra 592 C>T (3.4%), G6PD Union 1360 C>T (2.3%), G6PD Chatham 1003 G>A (2.3 %), G6PD Orissa 131 C>T (1.2%) and G6PD Andalus 1361 G>A (1.2%). All these alleles have previously been found in many other populations (Ganczakowski et al, 1995;Corcoran et al, 1992;Iwai et al, 2001;Hsia et al, 1993;Hirono et al, 1995;Vulliamy et al, 1988;Kaeda et al, 1995 andKotea et al, 1999) and it is difficult to speculate their origin. The data on these mutations which occur at low frequencies in the Malay population may be due to the different ancestral contributions to the present gene pool in multi-ethnic Malaysia or they could have arisen independently, as in various other populations.…”
Section: G6pd Mutations and The Anthropological Significancementioning
confidence: 93%
“…While the study did not quantitatively assess G6PD deficiency, other studies have found these mutations to be associated with ~10% [37], ~20% [37] and <10% [38] normal enzymatic activity, respectively. Across the wider Indian subcontinent, the G6PD variants Mediterranean, Gond and Kerala-Kalyan are widely distributed (although not common in any location) while the Orissa variant is found predominantly in eastern and southern India [37, 3944]. The Kerala-Kalyan variant has also been reported in individuals in southern Myanmar [18], Thailand (Phuket) and Mauritius [44].…”
Section: Discussionmentioning
confidence: 99%
“…Across the wider Indian subcontinent, the G6PD variants Mediterranean, Gond and Kerala-Kalyan are widely distributed (although not common in any location) while the Orissa variant is found predominantly in eastern and southern India [37, 3944]. The Kerala-Kalyan variant has also been reported in individuals in southern Myanmar [18], Thailand (Phuket) and Mauritius [44]. The genetic marker backgrounds in this study were also consistent with previous studies; the Kerala-Kalyan variant was linked to the 1311C/IVSXI C93T haplotype background and the Orissa variant to the 1311C>T/IVSXI C93 background.…”
Section: Discussionmentioning
confidence: 99%